Detection of Micrometasteses In Lymph Nodes in Cases of Carcinoma Breast by Immunohistochemistry - Sharma, Sunita; Mohanty, C S (Annals of Pathology and Laboratory Medicine, 2020)
Background – We evaluated archived lymph nodes of breast carcinoma for micrometastases detection by serial multiple sections (SMS) and immunohistochemistry (IHC) and found increased positive lymph nodes yield which led to change in staging in few cases, treatment and prognosis. Method – Metastatic free, early breast cancer cases of 36 patients with lymph node status pN0 or pN1 were evaluated. These were the cases had been treated with modified radicle mastectomy and axillary lymph node dissection. All the lymph node was cut at 50µm interval to get 5µm thick serial sections. These serial sections (SMS) were stained with Hematoxyline and Eosin (H&E). Out of these 2 sections were subjected to Immunohistochemistry (IHC). Monoclonal antibodies chosen for IHC were panCK (Cytokeratin) and EMA (Epithelial membrane antigen) to detect micrometasteses. Results – Total 463 lymph nodes from 36 cases of carcinoma breast were studied. New serial sections (SMS) cut from 435 lymph nodes of breast revealed 16(3.67%) additional positive lymph nodes from 12 cases. Out of 16 positive lymph nodes 4 were macrometasteses and 12 were micrometastases. Immunostaining with CK antibody revealed micrometasteses in 40 of 435 (9.19%) lymph nodes and by EMA antibody 33 of 435 (7.59%). Out of 40 micrometasteses 8 were positive for isolated tumor cells (ITC). We calculated the Z value and corresponding p value between the two methods as H&E versus SMS, H&E versus IHC and SMS versus IHC for carcinoma breasts. The tests revealed that SMS and IHC are definitely the superior methods in detection of a greater number of positive lymph nodes in cases of carcinoma breast. P value for detection of micrometasteses H&E versus SMS is <0.05 (S), H&E versus IHC <0.01(S) and SMS versus IHC (<0.02). Out of 36 cases 06 cases showed change in staging and 03 out of 06 cases were upstaged from early to advanced stage carcinoma. Conclusion – Significant number of metasteses are missed by routine processing of lymph nodes on H&E staining. SMS and IHC increase the yield of metasteses in lymph nodes. CK is superior marker than EMA.